Analysis of an herbal ayurdantham medicated tooth liquid on dentinal tubule occlusion using scanning electron microscopy - Ashwini Tumkur Shivkumar (Wolters Kluwer Medknow Publications, 2021)
Background: Dentin hypersensitivity is described as “short sharp pain arising from exposed dentin in response to various stimuli typically thermal, evaporative, tactile, osmotic or chemical and cannot be ascribed to any other form of dental defect or disease.” Dentine hypersensitivity can be treated with various desensitizing agents ,where oral rinse has a promising effect in delivering the therapeutic effect all over the tooth surface including interproximal areas, as they can flow and reach areas where toothpastes are not much effective, hence the occlusion of dentinal tubules using Ayurdhantam medicated an herbal mouthwash was evaluated. Methodology: Twenty such dentinal blocks were obtained; the surfaces of each dentin block were polished using a silicon carbide disc for 30 s to create a basic smear layer. The smear layer is finally detached by applying 17% EDTA solution onto the dentin blocks for 5 min to ensure the patency of the dentinal tubules, following which they were rinsed with distilled water. The specimens were placed into the Ayurdhantam solution (medicated) for 2 min every day for 7 days. The specimens were stored in artificial saliva during the study. The specimens were analyzed under scanning electron microscope (SEM) for the occlusion of dentinal tubules. Results: SEM images showed the partial occlusion of the tubules and a large amount of smear layer. Conclusions: Based on this in vitro experiment carried out, it is shown that Ayurdhantam-medicated mouthwash can be used for treating dentine hypersensitivity effectively.